The Effect of Mathematics Learning Interest and Social Skill on Algebraic Reasoning - Sucipto, Lalu; Syawahid, Muhammad; Afika, Dini Safitri Nur; Kasim, Marini (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
Algebraic reasoning plays a role in mathematical thinking. Understanding factor affective of algebraic reasoning is essential for improving mathematics education. This study aims to examine the effect of learning interest and social skills on students' algebraic reasoning. We conducted a quantitative study using a correlational design, employing questionnaires and a test as data collection methods. We selected 202 students from the Islamic state of junior high school in Mataram as a research sample using a simple random technique. The study used an algebraic reasoning test, a learning interest questionnaire, and a social skills questionnaire as research instruments. The data was analyzed using descriptive data and inferential analysis. Descriptive data consist of categorical descriptive and statistical descriptive. Inferential analysis used a multiple regression including prerequisite tests (normality, linearity, multicollinearity and heteroscedasticity) and hypothetical tests using t-test for partial and F-test for simultaneous. The result showed that learning interest has no effect on students algebraic reasoning (t-test =0,055, sig. = 0,957 > 0,05). Meanwhile, the social skills have an effect on students algebraic reasoning (t-test =2,943, sig. = 0,004 < 0,05). In addition, learning interest and social skill simultaneously have an effect on algebraic reasoning (F-test = 4,345, sig. = 0,014 < 0,05). The result also confirmed that learning interest and social skills have a 4,2% of contribution to increasing students algebraic reasoning. To improve the students learning interest and social skill, teacher should be encouraged in designing interactive learning and collaborative learning approaches, such as group discussions, peer tutoring, and cooperative problem-solving.